Growth opportunity and IPO value: An empirical study of Malaysian IPOs - Chui, Zi Ong; Mohd Rashid, Rasidah; Taufil Mohd, Kamarun Nisham (Universiti Kebangsaan Malaysia, 2020)
The offer price of Malaysian initial public offerings (IPOs) is mostly determined by fixed-price mechanism, indicating that information for investors regarding the actual value of an IPO is not being fully reflected in the offer price. The investors’ opinion in fact triggers IPO value on the first trading day in the market. This study aims to investigate the effect of growth opportunity on the pricing of Malaysian IPOs upon being listed on Bursa Malaysia. The sample of the study consists of 126 IPOs listed from January 2009 to December 2017. Through the analysis of cross-sectional and quantile regression in median and high quantiles, the study found a significant positive relationship between growth opportunity and total market value of IPOs. The findings suggest that IPOs which allocate a greater proportion of proceeds for firms’ future growth signal the firms’ quality, leading investors to trigger IPO value upwards during first-trading day. The findings have implications for the regulators, specifically the Securities Commission and Bursa Malaysia, to ensure that the information on the uses of proceeds revealed in IPO prospectuses is in line with the “Equity Guidelines” because this information gives impact on the investors’ decisions towards IPO subscription.